Implementation of Regulation of The Parliament of North Lampung Regency Number 16 Year 2014 Concerning Detailed Terms DPRD District North Lampung in Making Regional Regulations in North Lampung District - Lintje Anna Marpaung (Law Faculty of Universitas Bandar Lampung, 2018)
As a representative of the people, North Lampung Regency DPRD is a manifestation of community representatives of North Lampung Regency in the implementation of local government. In the case of the implementation of local government, the DPRD of North Lampung Regency must realize the aspiration of the people into the regional policy, one of which is the formulation of local regulations in accordance with the implementation of the North Lampung Regency DPRD Regulations. How the Implementation of North Lampung Regency DPRD Regulation No. 16 of 2014 on the Procedure of North Lampung Regency DPRD In Making Local Regulation, Factors that become obstacles for the DPRD in carrying out its role in the process of making local regulations, Efforts made by DPRD Kabupaten Lampung Utara To overcome the obstacles that exist in carrying out its duties and roles in the process of making local regulations. The method of research is the method of Juridical Normative and Juridical Empirical approaches, with data sources taken are secondary data and primary data, then analyzed qualitatively. Implemetation of North Lampung Regency DPRD Regulation No. 16 of 2014 on the Procedure of North Lampung Regency DPRD in making the regional regulation that is, the role of Local Legislation Body in making the local regulation either comes from local government and also the initiative of DPRD. It is expected that the DPRD members of North Lampung Regency can better understand the implementation of the DPRD Code of Conduct in local regulation making, following technical guidance related to the improvement of human resources capacity of DPRD members, the provision of experts, the role of political parties to be more selective in the recruitment process of candidates.